Study of antimicrobial activity of iodine coordination complexes against multidrug resistant bacteria (Experimental biology, 2018)
Nowadays in spite of increasing quantity of antimicrobial drugs in pharmaceutical market antibiotic resistance has become a global social and medical problem. Due to this fact the significance of new antibiotic-free drugs production and development for infectious diseases treatment caused by multiple resistant microorganisms has moved upward.Halogens provide bactericidal properties against Gram-positive and Gram-negative bacteria and also increase the lipophilicity of the drugs which leads to its light passage through biomembranes. The creation of complexes of organic compounds with halogens leads to the appearance of new bioactivities or a noticeable strengthening of the existing ones.The aim of this study was the investigation and screening of antimicrobial activity of original coordination complexes against multidrug resistant microorganisms for determination of the most effective antimicrobial agents. Original coordination compounds were obtained by the complexing reaction between lithium, potassium, iodine ions and organic ligands. As the test strains Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa microorganisms were used in this study.As a part of study, from 8 study samples of complexes it was found 3 coordination compounds that showed the highest antimicrobial effect against multidrug resistant strains.Obtained results provide perspective for further study in future production of antimicrobial drugs which would not cause the resistance of microorganisms and could be used for existing multidrug resistant strains.Key words: iodine coordination complexes, antimicrobial activity, multidrug resistant microorganisms.